Probing plasma wakefields using electron bunches generated from a laser wakefield accelerator. (1st March 2018) - Zhang, C J; Wan, Y; Guo, B; Hua, J F; Pai, C-H; Li, F; Zhang, J; Ma, Y; Wu, Y P; Xu, X L; Mori, W B; Chu, H-H; et al.
Abstract: We show experimental results of probing the electric field structure of plasma wakes by using femtosecond relativistic electron bunches generated from a laser wakefield accelerator. Snapshots of laser-driven linear wakes in plasmas with different densities and density gradients are captured. The spatiotemporal evolution of the wake in a plasma density up-ramp is recorded. Two parallel wakes driven by a laser with a main spot and sidelobes are identified in the experiment and reproduced in simulations. The capability of this new method for capturing the electron- and positron-driven wakes is also shown via 3D particle-in-cell simulations.